Energy performance of building envelopes integrated with phase change materials for cooling load reduction in tropical Singapore - Lei, Jiawei; Yang, Jinglei; Yang, En-Hua (Applied energy, 2016)
•PCM can effectively reduce building cooling load in tropical climate.•Selection of phase change temperature, location, thickness, and enthalpy curve of PCM is critical.•Optimum phase change temperature is influenced by location, thickness, and enthalpy curve of PCM.•Recommendation on the optimized use of PCM in tropical climate is provided. Phase change materials (PCMs) are capable to absorb massive heat during a phase transition in a narrow temperature range, which have great potential to be incorporated into building envelopes to prevent heat penetration into buildings and reduce cooling loads. The efficiency and selection of PCMs, however, are highly subject to the climate where they are applied. This study focused on the energy performance of building envelopes integrated with PCMs for cooling load reduction in tropical climate through numerical simulations. Studies were carried out to reveal the efficacy and factors that govern the performance of the PCM addition for cooling load reduction in Singapore. The results showed that PCM can effectively reduce heat gains through building envelopes throughout the whole year, indicating the significant advantage of the use of PCMs in tropics over other regions where PCMs are only effective in certain seasons. The selection of PCM with suitable phase change temperature is critical. PCMs applied to the exterior surfaces of walls showed better performance and the optimum phase change temperature is the lowest temperature allowing the full melting–solidification cycle of the entire PCM layer. A larger phase change temperature range improves the adaptivity of the PCMs to temperature variations, but may compromise the largest energy savings that the PCMs can achieve. While thicker PCM layer reduces heat gains through building envelope, thinner PCM layer shows higher efficiency and cost benefits.